Penatalaksanan Sindrom Metabolik pada Wanita Usia 60 Tahun dengan Pendekatan Dokter Keluarga - Afifah, Ria; Nusadewiarti, Azelia (Medula, 2025)
Metabolic syndrome is a cluster of risk factors including hypertension, dyslipidemia, central obesity, and insulin resistance that increase the risk of cardiovascular disease. Elderly individuals are particularly vulnerable due to physiological aging, reduced physical activity, and unhealthy dietary habits. This case report presents a comprehensive management of a 60-year-old female patient diagnosed with metabolic syndrome, consisting of hyperuricemia, hypercholesterolemia, and grade I hypertension. The patient presented to a primary care facility with complaints of shoulder pain and headache, and a sedentary lifestyle. Physical and laboratory examinations confirmed obesity class I (BMI 29.1), total cholesterol of 263 mg/dL, and uric acid level of 7.2 mg/dL. A multidisciplinary treatment approach was applied, combining pharmacological therapy (allopurinol, simvastatin, ibuprofen, and vitamin B12) with non-pharmacological interventions, including nutritional education, lifestyle modification, and aerobic exercise. Follow-up evaluations at two weeks and one month showed symptom relief, improved laboratory values, and enhanced patient knowledge and compliance. The integrated family medicine approach proved effective in improving the patient’s quality of life and awareness of long-term metabolic syndrome control.